Cassandre francoise. ([publisher not identified], 1615)
"Warning concerning the evil consequences of the marriages with Spanish heirs"--French Political Pamphlets Digital Collection, Brigham Young University.
First line of text ends with "vous" and page 16 has "FIN" at foot of page.
Signatures: A-B⁴.
Date of publication from Lindsay and Neu.
Caption title.
Lindsay, R.O. French political pamphlets, 1547-1648,entry 3238
Keywords: Politics and government. / fast / https://id.worldcat.org/fast/1919741; Diplomatic relations. / fast / https://id.worldcat.org/fast/1907412; Spain. / fast / https://id.worldcat.org/fast/1204303; France. / fast / https://id.worldcat.org/fast/1204289; France / History / Louis XIII, 1610-1643 / https://id.loc.gov/authorities/subjects/sh85051303 / Pamphlets. / https://id.loc.gov/authorities/subjects/sh99001703; Spain / Foreign relations / France / https://id.loc.gov/authorities/subjects/sh2008112245 / Early works to 1800 / https://id.loc.gov/authorities/subjects/sh99001366; France / Foreign relations / https://id.loc.gov/authorities/subjects/sh85051227 / Spain / https://id.loc.gov/authorities/names/n79006971-781 / Early works to 1800 / https://id.loc.gov/authorities/subjects/sh99001366; France / Politics and government / 1610-1643 / https://id.loc.gov/authorities/subjects/sh85051466; Pamphlets / https://vocab.getty.edu/aat/300220572 / France / https://id.loc.gov/authorities/names/n79006404-781 / Seventeenth century (dates CE). / https://vocab.getty.edu/aat/300404511 / aat; Early works. / fast / https://id.worldcat.org/fast/1411636